Virtual Training System for a MIMO Level Control System Focused on the Teaching-Learning Process - Gallardo Urbina, Andrea Estefanía (2023)
The present work is focused on the development of a Virtual Environment to perform the implementation of control algorithms in a MIMO level control learning module. The mathematical model is ob tained heuristically and to get the dynamic parameters of the system an identification and optimization algorithm is implemented. The environ ment has been developed using CAD tools and the UNITY 3D graphic engine, and MATLAB has been used for the control schemes. The pur pose of the developed system is to be a functional tool focused on the teaching-learning process in the industrial automation area that is safe and low-cost, especially when access to physical equipment is limited or does not exist.